Chiral (cyclopentadienone)iron complexes with a stereogenic plane as pre-catalysts for the asymmetric hydrogenation of polar double bonds. Issue 10 (8th March 2019) - Bai, Xishan; Cettolin, Mattia; Mazzoccanti, Giulia; Pierini, Marco; Piarulli, Umberto; Colombo, Valentina; Dal Corso, Alberto; Pignataro, Luca; Gennari, Cesare
Abstract: In this paper, we describe a small library of easy-to-prepare chiral (cyclopentadienone)iron pre-catalysts for enantioselective CO and CN hydrogenations. Starting from readily accessible achiral materials, six chiral (cyclopentadienone)iron complexes (1a-f ) possessing a stereogenic plane were synthesized in racemic form. Based on the screening of pre-catalysts (±)-1a-f in the hydrogenation of ketones and ketimines, we selected two complexes (1a and1d ) for resolution by semipreparative enantioselective HPLC. The absolute configuration of the separated enantiomers of1a and1d was assigned by XRD analysis (1a ) and by comparison between experimental and DFT-calculated ECD and ORD spectra (1d ). The enantiopure pre-catalysts ( S )-1a and ( R )-1d were tested in the asymmetric hydrogenation of several ketones and ketimines and showed good activity and modest enantioselectivity, the e.e. values ranging from very low to moderate (54%). Graphical abstract: Image 1